2014
DOI: 10.1007/s11033-014-3584-9
|View full text |Cite
|
Sign up to set email alerts
|

Mitofusin 2 deficiency leads to oxidative stress that contributes to insulin resistance in rat skeletal muscle cells

Abstract: Mitofusin 2 (Mfn2) is a dynamin-like protein anchored in the outer mitochondrial membrane that plays a crucial role in ensuring optimal mitochondrial morphological homeostasis. It has been shown that reduced expression of Mfn2 is associated with insulin resistance, but the mechanism is still unclear. We investigated whether Mfn2 deficiency leads to impaired insulin sensitivity via elevated oxidative stress. L6 skeletal muscle cells were treated with palmitate and Mfn2 expression was repressed by transfection w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 28 publications
7
30
0
Order By: Relevance
“…However, its action is crucial for cell life, possibly preventing an excess of close contacts between the two organelles that might result in a toxic transfer of Ca 2+ to mitochondria during cell stimulation (31) and eventually in cell death (38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…However, its action is crucial for cell life, possibly preventing an excess of close contacts between the two organelles that might result in a toxic transfer of Ca 2+ to mitochondria during cell stimulation (31) and eventually in cell death (38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…Mfn2, a mitochondrial fusion protein crucial for the maintenance of the mitochondrial network architecture, is induced during myogenesis and abundantly expressed in skeletal muscle [58]. Previous studies have suggested that mfn2 deficiency in muscles leads to mtDNA depletion, impaired OXPHOS, decreased mitochondrial membrane potential, and oxidative stress [59][60][61]. Moreover, muscle mfn2 protein levels were repressed in several catabolic conditions [62][63][64][65].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, in contrast to unsaturated fatty acids, saturated fats promote deregulation of food intake, increase body weight, obesity and are detrimental in the coordination of insulin sensitivity (Larsen and Tennagels, 2014). In vitro evidence has shown that stimulation with the saturated lipid, palmitic acid, promotes mitochondrial deregulation, oxidative stress and JNK and NFkB activation in muscle cells resulting in insulin resistance (Nie et al, 2014). Also, palmitic promotes ER stress activation in different cell types including neurons (Kwon et al, 2014;Nie et al, 2014;Yuzefovych et al, 2012).…”
mentioning
confidence: 99%
“…In vitro evidence has shown that stimulation with the saturated lipid, palmitic acid, promotes mitochondrial deregulation, oxidative stress and JNK and NFkB activation in muscle cells resulting in insulin resistance (Nie et al, 2014). Also, palmitic promotes ER stress activation in different cell types including neurons (Kwon et al, 2014;Nie et al, 2014;Yuzefovych et al, 2012). These evidences suggest that ER and mitochondria are primary targets of lipids leading to insulin resistance states and the development of metabolic disorders including obesity and T2DM.…”
mentioning
confidence: 99%
See 1 more Smart Citation